2023
DOI: 10.3389/fphar.2023.1096379
|View full text |Cite
|
Sign up to set email alerts
|

Dendrophthoe falcata (L.f.) Ettingsh. and Dendrophthoe pentandra (L.) Miq.: A review of traditional medical uses, phytochemistry, pharmacology, toxicity, and applications

Abstract: Dendrophthoe falcata (L.f.) Ettingsh. (DF) and Dendrophthoe pentandra (L.) Miq. (DP) have been traditionally used for the treatment of various ailments, such as cancer, ulcers, asthma, paralysis, skin diseases, tuberculosis, and menstrual troubles, in the ethnomedicinal systems of India and Indonesia. Currently, the chemical structures of 46 compounds have been elucidated from DF and DP, including flavonoids, triterpenes, tannins, steroids, open-chain aliphatics, benzyl derivates, and cyclic chain derivatives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 135 publications
0
7
0
Order By: Relevance
“…It has been observed that polysaccharides [30], and terpenoids (saponins) [31] are the primary components responsible for this effect [32][33][34]. Many of these compounds were also found to be present in D. falcata [35]. However, in this study, the compounds present in AE were not puri ed or characterized, making it challenging to predict the speci c compounds responsible for the observed adjuvanting activity.…”
Section: Discussionmentioning
confidence: 85%
“…It has been observed that polysaccharides [30], and terpenoids (saponins) [31] are the primary components responsible for this effect [32][33][34]. Many of these compounds were also found to be present in D. falcata [35]. However, in this study, the compounds present in AE were not puri ed or characterized, making it challenging to predict the speci c compounds responsible for the observed adjuvanting activity.…”
Section: Discussionmentioning
confidence: 85%
“…This species, together with D. pentandra (L.) Miq., has been used in the ethnomedicinal systems of India and Indonesia for the treatment of various ailments, including ulcers, asthma, paralysis, skin diseases, tuberculosis, and menstrual pain. D. falcata has been studied for its antimicrobial activity [ 101 , 102 ]. A review of 2023 reports shows studies on several properties, including the antioxidant effects through the inhibition of lipid peroxidation [ 103 ].…”
Section: The Asian Mistletoesmentioning
confidence: 99%
“… 2022 ; Kong et al. 2023 ). Its anticancer properties have been previously reported, especially against myeloma cells, while its antivirus activity has been reported to have antiviral activity against the Newcastle Diseases virus (Lazuardi et al.…”
Section: Introductionmentioning
confidence: 99%